2020
DOI: 10.1186/s12933-020-00997-7
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin improved systolic blood pressure, endothelial dysfunction and heart remodeling in the metabolic syndrome ZSF1 rat

Abstract: Background: Empagliflozin (empa), a selective sodium-glucose cotransporter (SGLT)2 inhibitor, reduced cardiovascular mortality and hospitalization for heart failure in patients with type 2 diabetes at high cardiovascular risk independent of glycemic control. The cardiovascular protective effect of empa was evaluated in an experimental model of metabolic syndrome, the obese ZSF1 rat, and its' lean control. Methods: Lean and obese ZSF1 rats were either non-treated or treated with empa (30 mg/kg/day) for 6 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
64
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 50 publications
4
64
0
1
Order By: Relevance
“…These effects can result in overall improvements in kidney disease and pathology, which is evident from lower hypertrophy and the histopathological analysis. Furthermore, it should be noted that polypharmacological characteristics of SAR442357 are similar to those of SGLT2 inhibitor empagliflozin reported in ZSF1 rats (Park et al, 2020). The latter has been approved as a treatment option for CKD/DKD patients.…”
Section: Discussionsupporting
confidence: 54%
“…These effects can result in overall improvements in kidney disease and pathology, which is evident from lower hypertrophy and the histopathological analysis. Furthermore, it should be noted that polypharmacological characteristics of SAR442357 are similar to those of SGLT2 inhibitor empagliflozin reported in ZSF1 rats (Park et al, 2020). The latter has been approved as a treatment option for CKD/DKD patients.…”
Section: Discussionsupporting
confidence: 54%
“…The consistent treatment effect of empagli ozin on mortality and cardiorenal and HF outcomes regardless of the MetS status expands previous ndings demonstrating consistent CV bene t across various subgroups. For example, it has been shown that empagli ozin reduced the risk of cardiorenal and mortality outcomes across subgroups based on the TIMI secondary prevention risk score as well as in those with or without HF and presumed resistant hypertension, and heart failure with reduced ejection fraction irrespective of diabetes and chronic kidney disease 5,[20][21][22][23] . Findings, that may be generalized to a large proportion of "real-world" patients 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Although an increasing number of studies on HFpEF have been conducted (Anker et al, 2019), more in-depth research on SGLT2 inhibitors in HFpEF is expected to be conducted in the future. In addition, SGLT2 inhibitors have significant therapeutic effects on hypertension (Park et al, 2020) and atherosclerotic disease (Nasiri-Ansari et al, 2018). Furthermore, recent studies have indicated that SGLT2 inhibitors enhance cardiac systolic function by improving myocardial energy production by directing myocardial fuel metabolism away from glucose synthesis toward ketone body (KB) formation (Ferrannini et al, 2016;Santos-Gallego et al, 2019).…”
Section: Keyword Analysismentioning
confidence: 99%
“…By inhibiting the protein SGLT2, which is expressed in the proximal convoluted tubule, SGLT2 inhibitors lower glucose levels independent of insulin action. Currently, SGLT2 inhibitors are recognized to possess a considerably broader scope of benefits in addition to simply hypoglycemic effects, including the induction of modest weight loss, natriuresis, and diuresis and reducing blood pressure (Zelniker and Braunwald, 2018;Park et al, 2020). Traditional antidiabetic drugs do not always reduce the cardiovascular (CV) complications of diabetes; however, the potential applications of SGLT2 inhibitors in CV disease (Docherty et al, 2020;Heerspink et al, 2020;Slomski, 2020) have attracted increasing intense research interest.…”
Section: Introductionmentioning
confidence: 99%